(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A rejected child is likely to bemore dependent to be clingy, intensely possessive, and to seek parentalapproval, nurturance, attention, and physical contact than the accepted child,because it seems or at least acceptance -rejection theory postulates that if achild’s “significant others” are rejecting, his needs for warmth and affectionare unfulfilled and he will, up to a point, increase his efforts to get loveand attention. In other words, he will become dependent. Beyond a certain pointthe dependency response may be extinguished or transformed. The seriouslyrejected child has not learned how to give love because he has never known aloving parent after whom he can model his own behavior, and for reasonsdescribed below, even though he craves affection he has difficulty acceptingit. In order to protect himself from more emotional hurt, the rejected childtends to wrap his emotions in cotton, to incest his emotions. Ultimately he maystop trying to get affection from the people who are important to him, that is,dependency responses disappear.